Social proof in social media shopping: an experimental design research - Abdul Talib, Yurita Yakimin; Mat Saat, Rafeah (2017)
The practices of social proof techniques to attract consumers to shop on social media have proliferated over time and been used extensively. The reviewed literature uncovers that social community recommendation, customers’ ratings and reviews, celebrity’s endorser and numbers of likes, affect consumers’ purchasing decisions. However, the effect of different types of social proof techniques on purchasing intention is unknown.This study empirically compares the effect of number of followers, celebrity endorser and social community recommendation on consumers’ purchasing intention.An experiment has been conducted and the results reveal that the consumers’ purchasing intention differs between groups.Further analysis discovers that the impact on consumers’ purchasing intention is different between high number of followers and low number of followers, and between having social community recommendation and not having social community recommendation.Though, the impact of these two techniques is equal wherein no technique is superior to other.In order to gain purchasing engagement and boost online sales, online businesses on social media are encouraged to use the power of social proof technique, either by increasing the number of followers or providing more social community recommendations.